In vivo and in vitro evaluation of marginal integrity in ceramic inlays - (:unkn) unknown (My University, 1996)
The marginal integrity is an important factor for the long-term success of ceramic inlays. The long term clinical performance of porcelain inlays depends on a number of factors of which the marginal adaptation is of significant interest. The aim of this study was to determine the margin quality of adhesively luted sintered porcelain inlays both in vivo and in vitro. MOD cavities without bevels were prepared on 10 extracted human mandibular molar teeth. Using the Ducera inlay system, inlays were fired on refractory dies and luted with a dual-curing composite resin. After polishing, each, tooth was sectioned in buccal/lingual and mesial/distal directions and marginal adaptation was assessed microscopically. The mean marginal gap of 78.77 +/- 14.85 microns recorded for occlusal margins was significantly smaller than that of 128.85 +/- 34.34 microns seen at the approximal margins. For in vivo evaluation, 25 fired porcelain inlays, including 7 onlays, were placed in Class II cavities. The assessment of the marginal adaptation of inlays was made according to the scaling system used by Aberg et al. (Acta Odontol Scand 1994; 52:140-149). In 19 of the clinical cases, the restoration was contiguous with the existing anatomic form. Both in vivo and in vitro evaluations showed the margin quality of porcelain inlays to be high.
Keywords: Adult; Female; Humans; Middle Aged; Male; Mandible; Dental Porcelain; Molar; Dental Cavity Preparation; In Vitro Techniques; Dental Marginal Adaptation; Inlays